Al2O3-coated porous separator for enhanced electrochemical performance of lithium sulfur batteries - Zhang, Zhiyong; Lai, Yanqing; Zhang, Zhian; Zhang, Kai; Li, Jie (Electrochimica acta, 2014)
Al2O3-coated separator with developed porous channels is prepared by coating Al2O3 polymer solution on routine separator. The batteries with Al2O3-coated separator exhibited a reversible capacity of as high as 593 mAh g-1 at the rate of 0.2C after 50th charge/discharge cycle. The enhancement in the electrochemical performance could be attributed to the reduced charge transfer resistance after the introduction of Al2O3 coating layer. Besides, the Al2O3 coating layer, acting as a physical barrier for polysulfides, can effectively prevent polysulfides shuttling between the cathode and the anode. We believe that the Al2O3-coated separator is promising in the lithium sulfur battery applications. •Al2O3-coated separator is used as the separator of lithium sulfur battery.•The cell with Al2O3-coated separator exhibits excellent cycling stability and high rate capability.•Al2O3-coated separator is promising in the lithium sulfur battery applications. In this paper, Al2O3-coated separator with developed porous channels is prepared to improve the electrochemical performance of lithium sulfur batteries. It is demonstrated that the Al2O3-coating layer is quite effective in reducing shuttle effect and enhancing the stability of the sulfur electrode. The initial discharge capacity of the cell with Al2O3-coated separator can reach 967 mAh g−1 at the rate of 0.2C. After 50th charge/discharge cycle, this cell can also deliver a reversible capacity of as high as 593.4 mAh g−1. Significantly, the charge-transfer resistance of the electrode tends to be reducing after using Al2O3-coated separator. The improved cell performance is attributed to the porous architecture of the Al2O3-coating layer, which serves as an ion-conducting skeleton for trapping and depositing dissolved sulfur-containing active materials, as confirmed by scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS).